Global reach The impact of the EIB beyond the European Union 2019 - European Investment Bank (European Investment Bank, 2020)
The greatest challenges we face to today are global. This is true for climate change and the need to build new models of sustainable and resilient development. It is equally true for the coronavirus pandemic that threatens to erode some of the progress made on poverty reduction around the world.As the world's largest multilateral development bank, the European Investment Bank (EIB) has the means, and the experience, to help nations outside of Europe meet these challenges. Our report, Global Reach: The Impact of the EIB beyond the European Union, looks at our projects outside of Europe that bring clean water, green energy, new infrastructure and funds for small and female-owned businesses.Our projects provide the kind of support societies need to advance, and to advance in a way that will last well into the future.